2021
DOI: 10.3389/fonc.2021.687333
|View full text |Cite
|
Sign up to set email alerts
|

A Nomogram for Preoperatively Predicting the Ki-67 Index of a Pituitary Tumor: A Retrospective Cohort Study

Abstract: BackgroundThe Ki-67 index is an indicator of proliferation and aggressive behavior in pituitary adenomas (PAs). This study aims to develop and validate a predictive nomogram for forecasting Ki-67 index levels preoperatively in PAs.MethodsA total of 439 patients with PAs underwent PA resection at the Department of Neurosurgery in Jinling Hospital between January 2018 and October 2020; they were enrolled in this retrospective study and were classified randomly into a training cohort (n = 300) and a validation co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
2
3
0
Order By: Relevance
“…Furthermore, age was also found to have an inverse association with an increased MIB-1 labeling index. This result is also in line with the findings of Cai et al [ 11 ]. They found that the mean age of patients with an MIB-1 labeling index ≥3% is significantly higher compared to those with an MIB-1 labeling index <3%.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, age was also found to have an inverse association with an increased MIB-1 labeling index. This result is also in line with the findings of Cai et al [ 11 ]. They found that the mean age of patients with an MIB-1 labeling index ≥3% is significantly higher compared to those with an MIB-1 labeling index <3%.…”
Section: Discussionsupporting
confidence: 93%
“…An increased MIB-1 labeling index implies an increased need to achieve maximum cytoreductive surgical therapy. To date, there are approaches such as machine learning models using T2 weighted magnetic resonance imaging (MRI) or nomograms combining clinical, demographic, and imaging characteristics to preoperatively estimate the MIB-1 labeling index [ 10 , 11 ]. However, no simple and quick-to-use scoring sheet exists so far to enable an estimation of the MIB-1 index prior to surgical resection.…”
Section: Introductionmentioning
confidence: 99%
“…(45,46) Moreover, we showed that tumors in the LARGE group had ki67 >3% two times more frequently than those in the non-LARGE group. These ndings were similar to other studies, such as the series of Cai et al that showed that the maximum dimension of the tumor was an independent risk factor for a high ki67 index (47). Nevertheless, this is controversial as other studies have shown no correlation (48), probably because of the difference in the tumor subtypes.…”
Section: Discussionsupporting
confidence: 89%
“…Except for nonfunctional PA, the results of Mohseni et al revealed that age was negatively correlated with the Ki-67 index level in patients with growth hormone-secreting PAs [ 19 ]. Ma et al have reported that the mean age of the low Ki-67 index group was significantly higher than that of the high Ki-67 index group [ 20 ]. Here, the mean age of the patients with a Ki-67 index < 3% was 56.94 ± 9.80 years, which was significantly higher than 50.46 ± 12.99 years of the patients with a Ki-67 index ≥ 3%.…”
Section: Discussionmentioning
confidence: 99%